Analyze the Calculation of the Cost of Production on the Selling Price of Suli 5 Bottled Drinking Water (AMDK) at CV. Sai Tenrisau Makassar City - Syahrayni Andi Syarifah (Economics and Digital Business Review, 2024)
This study aims to analyze the calculation of the cost of production on the selling price of Suli 5 bottled drinking water (AMDK) at CV. Sai Tenrisau Makassar City. The variables of this study are: (1) Cost of Production as the independent variable (X) and (2) Selling Price as the dependent variable (Y). The population in this study are employees of CV. Sai Tenrisau. Samoel in this study are employees related to the production cost of Bottled Drinking Water CV. Sai Tenrisau namely Finance and Administration Section, as well as the Production Section. Data collection is done through documentation and interviews. The data analysis technique that will be used in this research is descriptive quantitative. The results showed that the calculation of the cost of goods manufactured by the company did not follow the applicable accounting theory, and the determination of the company's selling price followed the prevailing market price.